Evaluation of three methods for estimating leaf area index of cowpea (Vigna unguiculata) (2011)
Leaf Area Index (LAI) is a concept that cuts across agricultural sciences and agricultural engineering with an encapsulating feature in environmental engineering. It is one of the most difficult to quantify properly owing to large spatial and temporal variability. This paper discusses briefly LAI and the use of three methods which are non-destructive in determination of its value for cowpea, namely: the empirical formulae, the graphical and the image processing methods. Cowpea seeds were planted and samples were marked for determination of LAI by the three methods. The results showed that image processing as a more accurate and promising method compared to the other two